Paracoccidioides lutzii Plp43 Is an Active Glucanase with Partial Antigenic Identity with P. brasiliensis gp43 - Leitão, Natanael P. (Public Library of Science, 2014)
BACKGROUND: Paracoccidioides brasiliensis and P. lutzii cause paracoccidioidomycosis (PCM). P. brasiliensis main diagnostic antigen is glycoprotein gp43, and its peptide sequence is 81% identical with a P. lutzii ortholog here called Plp43. P. lutzii (“Pb01-like”) apparently predominates in Midwestern/Northern Brazil, where high percentages of false-negative reactions using P. brasiliensis antigens have recently been reported. The aim of this work was to produce recombinant Plp43 to study its antigenic identity with gp43. METHODOLOGY: We expressed rPlp43 as a secreted major component in Pichia pastoris and studied its reactivity in immunoblot with PCM patients' sera from Southwestern and Midwestern Brazil. PRINCIPAL FINDINGS: We showed that rPlp43 is not glycosylated and bears glucanase activity. The protein did not react with anti-gp43 monoclonal antibodies in immunoblot, suggesting absence of the corresponding gp43 epitopes. Nevertheless, common epitope(s) might exist, considering that gp43-positive PCM sera recognized rPlp43 in immunoblot, while gp43-negative sera (33 out of 51) from patients resident in Midwestern Brazil were also rPlp43-negative. Two genotyped P. lutzii were from patients with gp43-negative sera, suggesting that non-reactive sera are from patients infected with this species. CONCLUSION: Our data suggest that gp43 and Plp43 bear one or only a few common epitopes and that gp43 cannot be used in diagnosis of PCM patients infected with P. lutzii probably because Plp43 is poorly expressed during infection.